Strategy SMP Muhammadiyah 2 Bangil in Learning Activities During the Covid-19 Pandemic - Cantika Diah Cahyani (Proceedings of The ICECRS, 2021)
This study aims to determine educational strategies in the midst of the Covid 19 pandemic. The Covid 19 pandemic has an impact on the world of education because this requires the learning process to be carried out online by utilizing technology. This research is a descriptive qualitative research. The data collection techniques in this study consist of the interview method, the observation method and the documentation method. The results of this study are what SMP Muhammadiyah 2 Bangil does, namely by changing the learning process system from face-to-face learning to online, and also at SMP Muhammadiyah 2 Bangil conducting face-to-face learning processes while still complying with health protocols. This distance learning maximizes the role of school principals, waka curriculum, waka student and teachers to interact with students and guardians of students by using applications such as WhatsApp as a medium of learning and communication.